The effect of strength training on the kinematics of the golf swing - Scarfe, A.; Li, F.; Bridge, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Despite the wide acceptance of resistance training in other sports, use of such programs in golf is a relatively new concept; consequently there is a lack of research addressing the effects of these programs on golfing performance. The few studies addressing this issue have used golf-specific programs (Lephart et al, 2007) these can require specialist equipment and can be more difficult to follow. Outcome measures in these studies have shown that strength training improves performance measures i.e. distance the ball is carried yet neglected details of the coordination of the golfer themselves (Fletcher and Hartwell, 2004). The aim of this study was to identify how a simple combined general resistance and plyometric program effects golf swing kinematics.